Digital Business Strategies in 360° Videobooth Services: Developing Entrepreneurial Opportunities in the Creative Industry - Mohammad Desta Juliano Cahaya Putra; Ni Made Ayu Natih Widhiarini; Bagus Wahyu Nirmala (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the digital business strategies implemented by Captain Video in developing competitive advantage and entrepreneurial opportunities in Bali’s creative tourism industry. Captain Video is a creative digital business that utilizes 360° videobooth technology to provide interactive, immersive, and social media-oriented documentation services. This research employed a descriptive qualitative method with a case study approach. Data were collected through observation, semi-structured interviews, documentation, and literature review involving ten informants consisting of the business owner, management staff, operational employees, and consumers. The findings reveal that Captain Video develops its competitive advantage by integrating immersive digital technology, social media marketing, creative content production, and customer experience-based services. The use of 360° videobooth technology enables the business to offer modern, engaging, and shareable visual experiences that align with consumer behavior in the digital era, particularly among millennials and young digital users. Digital marketing strategies through Instagram, TikTok, content marketing, and influencer collaboration support brand awareness, customer engagement, and market expansion. Furthermore, the study indicates that entrepreneurial opportunities in the creative tourism industry are strengthened by innovation capability, technological adaptability, digital competencies, and the ability to create memorable consumer experiences. Theoretically, this research contributes to the development of studies on digital entrepreneurship, technology adoption, social media marketing, and experience-based business innovation. Practically, the findings provide insights for creative entrepreneurs on the importance of integrating technology, innovation, and customer experience to build sustainable digital business models in tourism destinations such as Bali.